2023
DOI: 10.1002/acn3.51825
|View full text |Cite
|
Sign up to set email alerts
|

The kynurenine pathway relates to post‐acute COVID‐19 objective cognitive impairment and PASC

Abstract: ObjectiveTo determine the prevalence and natural history of post‐acute COVID‐19 objective cognitive impairment and function, and their relationship to demographic, clinical factors, post‐acute sequelae of COVID‐19 (PASC), and biomarkers.MethodsA total of 128 post‐acute COVID‐19 patients (age = 46 ± 15; 42% women, acute disease severity: not hospitalized: 38.6% mild: 0–1 symptoms, 52% 2+ symptoms; 9.4% hospitalized) completed standard cognition, olfaction, and mental health examinations 2‐, 4‐, and 12‐month pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Finally, we found that post-intervention KYN levels were significantly higher in older adults with high MCI risk compared to older adults with low MCI risk. Consistent with our finding, cognitive impairment has been associated with higher KYN levels in individuals with type 2 diabetes mellitus [ 47 ] and acute post COVID-19 individuals [ 48 ]. KYN levels increase in case of elevated pro-inflammatory cytokine concentrations, which stimulates its conversion from tryptophan by indoleamine-2,3-dioxygenase [ 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…Finally, we found that post-intervention KYN levels were significantly higher in older adults with high MCI risk compared to older adults with low MCI risk. Consistent with our finding, cognitive impairment has been associated with higher KYN levels in individuals with type 2 diabetes mellitus [ 47 ] and acute post COVID-19 individuals [ 48 ]. KYN levels increase in case of elevated pro-inflammatory cytokine concentrations, which stimulates its conversion from tryptophan by indoleamine-2,3-dioxygenase [ 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…Despite these associations, the nature of such observational studies means that it is difficult to establish causal, directional relationships between depression and cognitive function. Further, there is evidence that post-acute COVID-19 cognitive impairment can occur regardless of mental health symptoms in all acute severity groups [ 34 , 36 , 66 ]. This is consistent with findings from electronic health records: mental health symptoms such as anxiety and depression returned to normal within 2 months, but cognitive symptoms increased for at least 2 years [ 6 ].…”
Section: Mental Health and Relationship To Cognitionmentioning
confidence: 99%
“…The difference in these outcomes needs further exploration, including qualitative evaluation, but suggests that the lived experience and recovery of LC is likely to be complex and multifactorial. Irrespective of immunological recovery, other causes of poor health, including persisting organ damage, cognitive impairment 28 , and the mental health impact of significant illness, may be contributing and mean that full physical recovery may lag behind immune recovery.…”
Section: Discussionmentioning
confidence: 99%